High-intensity running during international male field hockey involves frequent changes of direction and repeated accelerations but seldom reaches sprint velocities - Goods, P. S. R.; Appleby, B.; Scott, B. R.; Peeling, P.; Galna, B. (The Journal of Strength and Conditioning Research, 2024)
The aim of this investigation was to quantify the characteristics of high-intensity running in international male field hockey. Player movement data were collected through wearable player tracking devices across 3 tournaments (17 matches) from 27 members of the Australian male field hockey team (totaling 266 player matches). Active duration (minute), high-intensity efforts (>2.5 m·s-2 for >1 second), repeated high-intensity efforts (=3 efforts with =45-second recovery between efforts), and sprints (>7 m·s-1) were extracted and aggregated for each player match. The duration, distance, mean and peak speed, mean change of direction and straightness for each high-intensity effort, and peak deceleration at the conclusion of each effort were calculated. Mixed-effects models were used to estimate the mean for each outcome (fixed effect), with random intercepts modeled for player and match. On average, players completed 42.2 high-intensity efforts and 2.1 sprints per match. High-intensity efforts were short (3.61 seconds, 12.9 m), failed to reach high velocities (average peak velocity: 4.8 m·s-1), and involved frequent changes of direction (56% of efforts were not straight). There were 4.7 bouts of repeated high-intensity efforts per player, per match (comprising 3.8 efforts, with 3.53 seconds per effort separated by 16.2-second recovery). Last, we also found that 29% of high-intensity efforts involved a high-speed deceleration (>3.5 m·s-2), and these occurred frequently when in conjunction with a >45° (86%) or >90° (89%) change of direction. We recommend practitioners focus on developing players' ability to repeatedly accelerate, decelerate, and change direction over short distances and adopt testing and monitoring programs that assess these qualities.